2012
DOI: 10.1007/s11746-012-2058-2
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Quality of Chemically‐Modified Soybean Protein Concentrate‐Based Adhesives in Particleboards from Rice Husks

Abstract: The aim of the present study was to upgrade the bonding quality and water resistance of medium-density particleboards based on rice husks (RH) as a wood substitute and soybean protein concentrate (SPC) as the binder via chemical modification of SPC. Alkali (A), citric acid (CA) and boric acid (BA) were used to modify proteins and the carbohydrate complex in SPC. The effect of chemical treatment performed on SPC was followed by Fourier transform infrared, differential scanning calorimetry, thermo-gravimetric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 18 publications
(80 reference statements)
4
35
0
Order By: Relevance
“…Since pH adjustment enables the adhesive penetration, the improvements in adhesive bonding strength with pH adjustment could be expected. In addition, previous researches showed that denaturation of soy proteins with NaOH increased their adhesive bonding strength and water resistance Sun and Bian 1999;Mo et al 2004;Ciannamea et al 2012). Alkali can break internal hydrogen bonds in the coiled protein molecule, which in turn unfolds and exposes many polar groups (hydroxyl and carboxyl side-chain groups), able to bond with exposed hydroxyl groups from the ligno-cellulosic substrate (Ciannamea et al 2010).…”
Section: Characterization Of the Bondlinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Since pH adjustment enables the adhesive penetration, the improvements in adhesive bonding strength with pH adjustment could be expected. In addition, previous researches showed that denaturation of soy proteins with NaOH increased their adhesive bonding strength and water resistance Sun and Bian 1999;Mo et al 2004;Ciannamea et al 2012). Alkali can break internal hydrogen bonds in the coiled protein molecule, which in turn unfolds and exposes many polar groups (hydroxyl and carboxyl side-chain groups), able to bond with exposed hydroxyl groups from the ligno-cellulosic substrate (Ciannamea et al 2010).…”
Section: Characterization Of the Bondlinesmentioning
confidence: 99%
“…However, the effectiveness of natural adhesives is often inferior compared to the synthetic ones. Therefore, the development of adhesives based on natural materials has focused on improving the mechanical properties and water resistance of the adhesive bonds with different processes, namely physical, chemical and enzymatic modifications, and extraction of materials in a form containing a high proportion of protein such as soy protein isolate (SPI), glycinin or conglycinin extracted from soy flour Kalapathy et al 1995Kalapathy et al , 1997Sun and Bian 1999;Huang and Sun 2000a, b;Zhong et al 2002;Kumar et al 2004;Mo et al 2004Mo et al , 2006Zhang and Hua 2007;Sun 2008, 2010;Li et al 2009;Ciannamea et al 2010Ciannamea et al , 2012Liu et al 2010;Qi et al 2012). Soy proteins have been recently considered as a petroleum polymer alternative in the manufacture of adhesives, plastics and various binders (Zhong and Sun 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that the bond strength of the non-porous THM bamboo was lower suggests that mechanical interlocking is also a strong contributor to bond strength. During the adhesive preparation stage the addition of alkali (pH adjustment to 10) causes partial denaturation of the tightly coiled protein molecules by breaking down hydrogen bonds Mo et al 2004;Ciannamea et al 2010Ciannamea et al , 2012. This increases the contact area of protein molecules and opens up many more polar groups for bonding with polar groups on the wood substrate (Ciannamea et al 2010).…”
Section: Bonding Mechanismsmentioning
confidence: 99%